Smoking Status of Faculty and Their Tobacco Cessation Counselling Advisory - Amrita Geevarghese; Jagan Kumar Baskaradoss; Tina N. Tsafa; Israel T Agaku (Elsevier, 2022)
Introduction: Health professionals' own beliefs and practices, especially their smoking status, has been described to strongly influence their willingness to provide brief tobacco interventions (5 A's) to their patients. This study examines the association between the smoking status of faculty members in US dental programmes and (1) practice pattern; (2) perceived confidence; and (3) perceived educational preparedness of new graduates in providing the 5 A's to their patients. Methods: This study presents data from the National Tobacco Survey of Personnel in Dental and Allied Academic Programs (TSPDAP) conducted in 2018. Faculty members in US dental/allied dental schools were invited to participate in this survey. Data were stratified based on the smoking status of the respondents as "never" and "ever" smokers (smoked <100 and ≥100 cigarettes during their lifetime, respectively). Multiple logistic regression models were used to calculate the adjusted odds ratios (aORs) and 95% confidence intervals (CIs). Results: Data of 1896 participants were analysed, of whom 1032 (54.4%) were categorised as "ever" smokers. In the final regression model, low perceived barrier score was significantly associated with high practice pattern (aOR, 0.94; 95% CI, 0.92-0.97), high perceived confidence (aOR, 0.92; 95% CI, 0.90-0.95), and high perceived educational preparedness (aOR, 0.97; 95% CI, 0.94-0.98) in delivering the 5 A's to patients. Similarly, high perceived effectiveness was significantly associated with high practice pattern (aOR, 1.08; 95% CI, 1.05-1.11), high perceived confidence (aOR, 1.10; 95% CI, 1.06-1.13), and high perceived educational preparedness (aOR, 1.06; 95% CI, 1.03-1.09) in delivering the 5 A's to their patients. The smoking status of the dental personnel did not show any significant association with practice pattern, perceived confidence, or perceived educational preparedness in delivering the 5 A's to their patients. Conclusions: The smoking status of oral health care personnel was not significantly associated with their participation in tobacco cessation interventions.